2018
DOI: 10.4067/s0718-221x2018005031301
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and ftir spectroscopy of thermally compressed eucalyptus wood panels

Abstract: In this study, the change in the chemical properties of the thermally modified eucalyptus (Eucalyptus camaldulensis) wood boards were examined by wet chemical analysis and FTIR spectroscopy. The eucalyptus wood boards were modified with a laboratory type hot-press for four different groups at press pressures of 2 or 4 MPa and temperatures of 150°C or 180°C and compared to untreated control. After this, hot water, 1% NaOH, ethanol-cyclohexane, ethanol, and methanol-water solubility values were determined for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
2
20
1
Order By: Relevance
“…was investigated and presented the chemical composition of selected species of exotic wood derived from the region of Africa and the results are not identical but almost similar observation with this research. Almost similar lignin, holocellulose and alpha-cellulose content in eucalyptus (Eucalyptus camaldulensis) wood was also examined and reported byGonultas et al (2018).…”
mentioning
confidence: 52%
“…was investigated and presented the chemical composition of selected species of exotic wood derived from the region of Africa and the results are not identical but almost similar observation with this research. Almost similar lignin, holocellulose and alpha-cellulose content in eucalyptus (Eucalyptus camaldulensis) wood was also examined and reported byGonultas et al (2018).…”
mentioning
confidence: 52%
“…The signal at 1665 cm -1 corresponds to the carbonyl's vibrations in the aromatic absorption region [15]. The intensity at 1505 cm -1 showed C=C stretching in the aromatic ring absorption region [16]. The peak at 1457 and 1461 cm −1 was assigned to C-H bending vibration.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysis Of Cmentioning
confidence: 97%
“…The recovered lignin and commercial organosolv lignin were characterized according to C-H stretching in CH 2 and CH at 2928 and 2936 cm -1 [13]. The absorbance at 2930 and 2898 cm -1 was associated with the vibrations of the C-H group in methyl and methylene group [14]. The vibrations at 1711 cm -1 were related to C=O stretching of carbonyl groups' absorption region in recovered lignin and commercial organosolv lignin.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysis Of Cmentioning
confidence: 99%
“…Fourier Transform Infrared Spectroscopy (FTIR): FTIR analysis indicated that TN contained cellulose, hemicelluloses and lignin as expected. 3400-3330 cm -1 OH stretching of alcohols, phenols, and acids (Tjeerdsma & Militz, 2005;Müller et al, 2009;Esteves et al, 2013;Mattos et al, 2015;Missio et al, 2015;Gonultas & Candan, 2018). 2970-2820 cm -1 C-H stretching in methyl and methylene groups (Müller et al, 2009;Esteves et al, 2013;Gonultas & Candan, 2018).…”
Section: Acid-insoluble Lignin Determinationmentioning
confidence: 99%
“…3400-3330 cm -1 OH stretching of alcohols, phenols, and acids (Tjeerdsma & Militz, 2005;Müller et al, 2009;Esteves et al, 2013;Mattos et al, 2015;Missio et al, 2015;Gonultas & Candan, 2018). 2970-2820 cm -1 C-H stretching in methyl and methylene groups (Müller et al, 2009;Esteves et al, 2013;Gonultas & Candan, 2018). 1650-1652 cm -1 bands are absorbed water molecules of C=O stretching of the aromatic structures (Kotilainen et al, 2000;Nuopponen, 2005;Ozgenc et al, 2017).…”
Section: Acid-insoluble Lignin Determinationmentioning
confidence: 99%